Accurate Evaluation of Steady-State Sheath Voltage and Current in HVDC Cable Using Electromagnetic Transient Simulation - Mansoor Asif; Ho-Yun Lee; Kyu-Hoon Park; Bang-Wook Lee (Energies, 2019)
The current and voltage in High Voltage DC (HVDC) line is not pure DC but contain superimposed ripple components. The current ripple in core of HVDC cable magnetically induces a voltage in the sheath, whereas the voltage ripple causes the flow of charging current from core to sheath. The knowledge of sheath voltage is necessary to ensure compliance with the specification of utility companies. In this work, we have reported that the models available in commercial Electromagnetic Transient (EMT) simulation software erroneously introduce a DC bias in steady-state sheath voltage and sheath current. We have also demonstrated that by removing the DC bias accurate steady-state evaluation of sheath voltage and sheath current is possible. Additionally, we have analyzed the sheath voltage and currents in HVDC cable considering different cable lengths and sheath grounding schemes. It has been found that grounding the sheath at the terminal of HVDC cable can limit the sheath voltage to acceptable levels without causing substantial joule loss in the sheath.